Research: getting the right balance for wildfowl and wetlands - O’Connell, M (Wildfowl, 1999)
Many species, habitats and ecosystems are subject to a wide variety of anthropogenic influences. This has given rise to a broad diversity of conservation and management problems around the world, and the scientific community undertakes a range of applied research programmes that reflects this diversity of conservation needs. However, there is also a large body of what is often termed pure research, for which there are no explicit conservation objectives or end-users, but which nevertheless provides information that is fundamental to many areas of applied conservation. This paper discusses obtaining a balance between focusing limited conservation research resources on species where there is a need to prevent their imminent extinction, while at the same time recognising the need for providing population monitoring for more abundant species and a foundation of species and ecosystem knowledge that facilitates a conservation approach based on prevention rather than cure. Thus it is argued that because current abundance does not provide a guaranteed protection from extinction or population decline, and because we need to understand the processes that lead to population changes, there is a strong argument for developing balanced research programmes that include both threatened and presently abundant species. The potential difficulties both in achieving a balanced approach between pure and applied research, and in formulating research priorities in the light of limited and patchy conservation research funding, are also discussed.